1979
DOI: 10.1111/j.1365-2818.1979.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

A new inexpensive specimen carrier for freeze‐fracturing

Abstract: This paper describes the production and use of a new specimen carrier for the Balzers freeze-fracturing unit. The carriers are inexpensive, easily produced and have excellent mechanical and thermal properties. The rectangular form of the carriers provides easy handling and unequivocal orientation of anisotropic specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The stamping device produces hat-shaped sample-holders as proposed by Gulik-Krzywicki & Costello (1978). For an equivalent thickness, this shape presents a higher mechanical rigidity than the U shape proposed by Muller & Pscheid (1978). In the stamping device described here the mechanical tolerances are studied in order to provoke a cold-hammering of the cylindrical walls during the forming which increases their mechanical rigidity.…”
Section: Discussionmentioning
confidence: 96%
“…The stamping device produces hat-shaped sample-holders as proposed by Gulik-Krzywicki & Costello (1978). For an equivalent thickness, this shape presents a higher mechanical rigidity than the U shape proposed by Muller & Pscheid (1978). In the stamping device described here the mechanical tolerances are studied in order to provoke a cold-hammering of the cylindrical walls during the forming which increases their mechanical rigidity.…”
Section: Discussionmentioning
confidence: 96%
“…The samples were examined with a Philips EM 300 electron microscope, operating at 80 kV. For freeze-fracture experiments the vesicles were deposited on phosphor bronze specimen carriers, prepared by the method of Mueller and Pscheid [18] and immediately quenched in a slush of solid and liquid nitrogen. The samples were fractured at -160~ in a freeze-fracture device as described elsewhere [31].…”
Section: Methodsmentioning
confidence: 99%
“…The cells appear to be kept by microvilli at a distance from the substratum in all figures. x 18,000. advantage of using very thin free-fracture holders, mainly from copper (Pfenninger & Rinderer, 1975;Moor et al, 1976;Gulik-Krzywicki & Costello, 1978;Muller & Pscheid, 1978). (4) Furthermore, a cryogen jet was already used by Riehle (1968), Moor et al (1976, Burstein & Maurice (1978).…”
Section: Comments On New Methodsmentioning
confidence: 99%
“…Umrath, 1977). In a separate communication (Muller & Pscheid, 1978) it was already shown that object holders should be of Table 1. Cooling rates [K s-l]* (determined with thermocouples in the range between 293 K and 193 Kt).…”
Section: Preparation Of Cell Cultures F O R Fast Freezingmentioning
confidence: 99%
See 1 more Smart Citation